Peranan Guru Kelas Pada Masa Pandemi Covid 19 Dalam Sistem Pembelajaran Luring Pada Mata Pelajaran IPS DI SD 097359 Pondok Baru - Gultom, Narmawati; Asnewastri, Asnewastri; Hutauruk, Ahmad Fakhri Hutauruk (Jurnal Pendidikan Sejarah Humaniora dan Ilmu Sosial, 2023)
This study aims to examine the role of class teachers during the COVID-19 pandemic in the offline learning system in Social Studies (IPS) subjects at SD 097359 Pondok Baru. The COVID-19 pandemic, which requires learning to be carried out in a limited manner and without direct face-to-face meetings, presents a major challenge for teachers in delivering lesson materials, especially in IPS subjects. The method used in this study is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results of the study show that class teachers have a very important role in developing effective learning strategies, assisting students in understanding the material, and motivating students to remain active even though learning is carried out offline. Teachers also play a role in communicating with parents to ensure that children's learning processes continue to run smoothly. Although there are limitations in terms of accessibility to technology and supporting facilities, the role of teachers in providing guidance, providing easily accessible materials, and utilizing communication media such as telephones and WhatsApp groups has proven effective in supporting IPS learning. This study concludes that despite the major challenges faced during the pandemic, the role of class teachers remains crucial in maintaining the continuity of quality learning.